Oral health disorders among visually impaired children in South Asian countries: a systematic review - Mehta, Vini; Selvaraj, Siddharthan; Tripathy, Snehasish; Mishra, Neeta; Negi, Sapna; Mathur, Ankita; Tabnjh, Abedelmalek Kalefh (Frontiers in Oral Health, 2025)
Background and aimDespite the convergence of visual impairment and poor oral health among children, there is a scarcity of data on the common oral health disorders and their prevalence among children with visual impairments in South Asia. The purpose of this systematic review is to synthesize the existing literature on oral health diseases in visually impaired children in South Asia.MethodsAn exhaustive literature search was carried out in PubMed-MEDLINE, Scopus, Embase and Google Scholar from inception till 31st December, 2024. We included studies if they fulfilled the following criteria: visually impaired children (aged <18 years); assessment using dental examination; children with no other impairment from South Asian regions. Due to the high variability across age groups within the target population, we have synthesized and presented the data in a narrative format.ResultsThe search across databases yielded a total of 1,681 studies, out of which 9 studies were included. The prevalence of dental caries was reported ranging from 40% to 98.5%, and dental trauma ranged from 4.62% to 44.28%. High prevalence of malocclusion and gingivitis has also been reported. Quality assessment showed that three studies had medium risk of bias and remaining had a low risk of bias.ConclusionIn the South Asian region, it is crucial to make special needs dentistry widely accessible, provide caregivers with sufficient dental health information, and ensure dentists receive specialized training to enhance the effectiveness, comfort, and satisfaction of treatment.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=582083, PROSPERO (CRD42024582083).